To Determine the Effectiveness of Ranibizumab in Patients with Branch and Central Retinal Vein Occlusion: A Hospital Based Study: Doi:10.36351/pjo.v41i2.1904 - Memon, Ronak Afza; Fariha Sherwali; Shehnilla Shujaat; Waqas Ali; Asra Talpur (Pakistan Journal of Ophthalmology, 2025)
Purpose: To determine the effectiveness of ranibizumab in patients with branch and central retinal vein occlusion in a tertiary care hospital. Study Design: Interventional case series. Place and Duration of Study: Sindh Institute of Ophthalmology and Visual Sciences, Hyderabad.from July 2023 to March 2024. Methods: Patients of either gender and aged at least 20 years, diagnosed with macular edema (ME) secondary to CRVO or BRVO and best corrected visual acuity (BCVA) of less than 6/9 were included in the study. Patients with known retinal diseases, infection or previous treatment with laser photocoagulation, or a history of anti-VEGFinjections or corticosteroids in the last 6 months were excluded. Three intravitreal ranibizumab injections were givenat monthly intervals. The effectiveness of ranibizumab injection was investigated by measuring the difference in meancentral macular thickness and BCVA at 0, 3,6and 9months. Data was analyzed using SPSS version 25. Results: Total 188 patients were included with mean age of 57.53±10.74 years. Majority were males (63.8%) and 59% had disease in the right eye. Injections were administered to 158 patients (84%)for three months, while 30 (16%) patients required injections forsix months. The mean central macular thickness was 541.54±146.99 before injection, and 270.99±82.10, 240.02±22.50, 234.73±18.06 at 3, 6,and 9months,respectively. The mean BCVA (LogMAR) was1.21±0.57 before injection, 0.30±0.27 at 3 months, 0.21±0.16 at 6 monthsand 0.17±0.14at 9 months. Conclusion: Ranibizumab is effective in decreasing central macular thickness and improving BCVA in patients with macular edema following retinal vein occlusion.